Hot flushes and sweating, sleep problems, joint and muscular discomfort, and physical and mental exhaustion in breast cancer survivors during the first 24 months of tamoxifen therapy: a prospective observational study - Sung, Sumi; Min, Yul Ha; Park, Seul Ki; Lee, Sae Byul (Frontiers in Oncology, 2022)
Purpose: This study aimed to explore symptom trajectories over 24 months for hot flushes and sweating, sleep problems, joint and muscular discomfort, and physical and mental exhaustion experienced by premenopausal women diagnosed with tamoxifen-treated breast cancer. Methods: A total of 104 patients participated in the study. The menopausal symptoms were examined using the Menopausal Rating Scale at baseline, 3–6, 12, and 18–24 months after initiating tamoxifen. The changes over four time points were analyzed using repeated measures analysis of variance. The chi-square test was used to examine the differences between “no symptom-to-mild” and “moderate-to-extremely severe” 3–6 months after initiating tamoxifen according to the patients’ chemotherapy treatment experiences. Results: All menopausal symptoms occurred in > 70% of patients with breast cancer and persisted until 24 months. More than 50% of patients experienced four menopausal symptoms, with at least two at a serious severity level after initiating tamoxifen. Hot flushes and sweating occurred in the highest number of patients, recording high scores. Sleep problems and physical and mental exhaustion exhibited relatively high scores, even before tamoxifen initiation. There were significant changes over four time points in all symptoms. Young patients aged < 40 years experienced more severe sleep problems, and patients who had previously received chemotherapy experienced more severe joint and muscular discomfort. Conclusions: This study’s findings may assist in alerting healthcare providers to menopausal symptoms that develop during tamoxifen therapy and the need for early and active intervention to minimize symptom occurrence and distress.